Let the Whole Earth Sing Praise - DePaola, Tomie 1934- (New York : G.P. Putnam's Sons, 2011)
Combines text inspired by Old Testament Scripture with folk art-style illustrations in the tradition of Mexico's Otomi cultural art, in a tribute to the beauty of God's creations.
Keywords: Creation